International Risk Sharing During the Globalization Era - Matsumoto, Akito (IMF Working Papers; Working Paper ;, 2009)
Though theory suggests financial globalization should improve international risk sharing, empirical support has been limited. We develop a simple welfare-based measure that captures how far countries are from the ideal of perfect risk sharing. We then take it to data and find international risk sharing has, indeed, improved during globalization. Improved risk sharing comes mostly from the convergence in rates of consumption growth among countries rather than from synchronization of consumption at the business cycle frequency. Our finding explains why many existing measures fail to detect improved risk sharing-they focus only on risk sharing at the business cycle frequency.